Influence of pelvic lymphadenectomy on selected perioperative parameters in patients with stage I endometrial cancer - Obrzut, Bogdan; Skręt, Andrzej; Obrzut, Marzanna; Ulman, Dariusz; Król, Piotr (Menopause Review/Przegląd Menopauzalny, 2009)
Objective: The aim of the study was to evaluate the influence of pelvic lymphadenectomy on selected perioperative parameters in patients diagnosed with endometrial cancer. Material and methods: The prospective cohort study comprised a group of 118 patients diagnosed with endometrial cancer FIGO I, who were undergone abdominal hysterectomy with adnexectomy and staging. 42 patients were additionally undergone pelvic lymphadenectomy, while the others (76 patients) were not because they had not indications to do it. In both groups there was evaluated time of operation, postoperative complications, loss of blood (hemoglobin), postoperative fever and time of hospitalization. Statistical analysis was performed with the Student’s t-test and the c2 test. Results: In the group of patients who were undergone lymphadenectomy, intraoperative hemorrhagic complications were noticed in 2 cases (4.8%), while in the group of patients without lymphadenectomy, the hemorrhage occurred only in 1 case (1.3%). Blood loss (loss of hemoglobin) was not higher significantly in the group of patients with pelvic lymphadenectomy. Postoperative fever occurred only in 4 patients from the lymphadenectomy group and in 10 without lymphadenectomy. Pelvic lymphadenectomy prolongs significantly time of operation (average 18.4 minutes), but does not prolong time of hospitalization. Conclusions: Pelvic lymphadenectomy in patients diagnosed with endometrial cancer FIGO I does not increase intraoperative loss of blood (hemoglobin), percentage of intraoperative complications, postoperative infections as well as time of hospitalization. Pelvic lymphadenectomy significantly prolongs time of operation.